Reply to comments by Wood, Hewer and Belcher on 'Stably Stratified Boundary–Layer Flow over Low Hills: a Comparison of Model Results and Field Data' (1997) - Weng, Wensong (Boundary-layer meteorology, 1998)
I appreciate Wood, Hewer and Belcher's interest in my paper. Their comments on the paper focus on two subjects: the concepts and formula used to define the middle-layer height, h sub(m) , and an argument that wavenumber-dependent scaling should be used instead of bulk scaling in stable boundary-layer flow over hills. The original definition of the middle layer is that part of the effectively inviscid outer region, where the velocity shear (velocity curvature) has a dominant effect on the (vertical) velocity perturbation (see Hunt et al., 1988a, for neutrally stratified flow, and 1988b, for stably stratified flow, referred to here as HLR and HRB respectively).